Cold hard truth on men, women & money : 50 common money mistakes and how to fix them - O'Leary, Kevin, 1954- (Gallery Books, 2014)
From bestselling author and television superstar Kevin O'Leary comes a new financial guide that takes you through money mistakes at every stage of life and teaches you how to avoid them. Don't spend too much. Mostly save. Always invest. This is simple advice, but it's often the simple advice that's easy to swallow and hard to follow. Kevin O'Leary understands that getting a handle on your personal finances can be challenging at any age. Whether you're a parent struggling to explain savings to your children, a student contemplating a big loan to pay for school, a newly engaged couple considering joint bank accounts, or a baby boomer entering retirement, Kevin offers solid, practical advice to help you make and keep more money. As a lead shark on ABC's Shark Tank, Kevin's success with money management and in business is legendary. But he's made mistakes along the way, too, and he's written this book so others can benefit from his experiences and learn how to avoid debt, how to save money, and how to invest for a brighter future. Each chapter is geared to a specific age or stage in life and looks closely at your relationship with money and how simple changes in thinking and decision-making can result in more cold hard cash in your wallet or bank account. You'll find real-life examples of common money mistakes and strategies for avoiding them, "Cold Hard Truth" quizzes and charts aimed at boosting your financial wisdom, and tips and tricks for making more money and growing it faster to achieve financial freedom. - Publisher.